Perceived Behavioural Control and Subjective Norms Influence Entrepreunial Intention - Ramdani, Muhammad Fathullah; Puspita, Dinda Sri; Permana, Intan; Maulani, Galih Abdul Fatah; Hamdani, Nizar Alam (Entrepreneurship Faculty, Universitas Garut, 2024)
Entrepreneurial intent is the desire or motivation of an individual to become an entrepreneur and start a business or venture. Among various age groups, Indonesia's Gen Z generation is known to have an interest in entrepreneurship that is below the average 1.60% of 18.94%. To increase entrepreneurial interest among Gen Z, an approach is needed, as well as the creation of an environment that develops entrepreneurial potential. This study used a survey distributed online and in person to 115 randomly selected respondents, with response rate of 50.4% and a total of 73 respondents recorded, representing approximately 30.43%. Therefore, the sample size for this study was 58 respondents who provided varied assessments for all items, and the researchers also divided the respondents into groups based on their age, specifically Generation Z. The researcher distributed the questionnaire through direct surveys and online distribution. The tool used by researcher to obtain respondents was a physical questionnaire, which was distributed directly to the respondents. The program used to analyze the data using regression analysis was Statistical Product and Service Solution (SPSS) to meet the criteria for data analysis using regression, which was applied on interval-scale data. The researcher performed arithmetic calculations on the data collected from the respondents. The research results were accurate and reliable with a significance level of 95%. The research findings pertain to the influence of perceived behavioral control and subjective norms on entrepreneurial intention. Based on the results of this study, it is hoped that the findings will be beneficial to the respondents and readers for further research.